Affiliate marketing in Museum Blockbuster Surabaya: A marketing communication perspective - Yudiana Indriastuti; Wahyuni; Diana Amalia (Jurnal Studi Komunikasi, 2024)
The COVID-19 pandemic has triggered an unparalleled crisis in the global tourist sector, demanding swift and imaginative adjustments for survival. This research examines the essential requirement for efficient digital marketing strategies, emphasising the increasing significance of affiliate marketing through E-Commerce and Online Travel Agents (OTA). This study analyses the Surabaya Blockbuster Museum (MBS), focusing on cinema and gaming enthusiasts from Generation X and Generation Y. This prompt analysis utilises a quantitative methodology, examining ticket sales data and MBS visitor surveys to understand the evolving preferences in ticket acquisition through E-Commerce or OTA platforms. Emphasis is placed on the vital elements of pricing and advertising during these uncertain times. Research indicates that Shopee and Goers are the favoured platforms for ticket acquisitions, with cost as the primary factor in platform choice. The study emphasises the efficacy of MBS's planned use of its official Instagram account for conveying price discounts, highlighting the crucial importance of social media in modern marketing initiatives. This study offers essential insights into the significance of pricing and promotional methods in affiliate marketing amid a global health crisis. The findings provide imperative and practical insights for tourist sector stakeholders facing difficulties due to the epidemic. This study elucidates efficient digital marketing techniques and the significance of flexible adaptation to global conditions, contributing to the critical conversation on the recovery and resilience of the tourist sector under unprecedented change.